2017
DOI: 10.1109/tsmc.2016.2578879
|View full text |Cite
|
Sign up to set email alerts
|

Agent Cooperation Mechanism for Decentralized Manufacturing Scheduling

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The latter acknowledges the flow and development of information as opposed to the optimisation model which addresses the agents' objective functions (Nedic & Ozdaglar, 2009;Saeidlou et al, 2019b). Previous work by the authors has demonstrated encouraging findings regarding decentralised GA optimisation acquired through the use of REPAST (Jules & Saadat, 2017). The functions of a multi-agent system can be defined through agent-based modelling (Abar et al, 2017), which when implemented can assist in the resolution of naturally distributed problems requiring a variety of customised computation entities (M. Wang et al, 2009).…”
Section: Optimisation Of a Multi-agent Systemmentioning
confidence: 99%
“…The latter acknowledges the flow and development of information as opposed to the optimisation model which addresses the agents' objective functions (Nedic & Ozdaglar, 2009;Saeidlou et al, 2019b). Previous work by the authors has demonstrated encouraging findings regarding decentralised GA optimisation acquired through the use of REPAST (Jules & Saadat, 2017). The functions of a multi-agent system can be defined through agent-based modelling (Abar et al, 2017), which when implemented can assist in the resolution of naturally distributed problems requiring a variety of customised computation entities (M. Wang et al, 2009).…”
Section: Optimisation Of a Multi-agent Systemmentioning
confidence: 99%
“…An optimized and decentralized scheduling mechanism is proposed based on agents such as order agent, product agent and resource agent [20]. The order agent generates process execution knowledge, product agent generates production knowledge, and resource agent generates process knowledge.…”
Section: B Smart Factory Schedulingmentioning
confidence: 99%
“…The ACM sub-module is inspired by the scheduling mechanism presented in a related study [20]. In smart factory environment, we consider multiple manufacturing machine networks.…”
Section: Proposed Acm-fef Scheduling Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, coalition formation has become a highly active topic in the field of MAS and has been successfully applied in operation research and computer science [7]- [9]. However, the traditional coalition formation concentrates on a very harsh term that each agent can only be a member of one coalition at any given time [6], which may result in a very low utilization rate of agents' resources [10].…”
Section: Introductionmentioning
confidence: 99%